REVIEW ON ENVIRONMENTAL DEGRADATION OF PETROLEUM HYDROCARBONS IN MARINE ENVIRONMENT - AMEETA SHARMA,; BHAGYASHREE PAREEK, (International Journal of Pharma and Bio Sciences, 2014)
Biodegradation is a process of breakdown of organic compounds into simpler compounds with the help of enzymes. Marine environment get contaminated by Petroleum hydrocarbons and these contaminates are removed by methods like chemical method but these are harmful to marine life through its toxic components. Another method is biological method in which degradation has been done with the help of microorganisms. In this process many bacteria take part for degradation because the composition of oil is different so single bacteria cannot degrade whole oil spill. Degradation can be done by two ways; aerobic degradation and anaerobic degradation, both processes have been done by different mechanisms and pathways because various types of bacteria are used in the process and other factors such as temperature, concentration etc are also variable. Despite of all this, still scientist need to understand more on highly toxic compounds like PAHs and photodegradation which is also very essential topic for consideration.